Modified predictive torque control for balancing three-level NPC inverter-fed PMSM drives - Hakami, Samer Saleh; Lee, Kyo Beum (Journal of Power Electronics, 2024)
The conventional approach of predictive torque control (PTC) is frequently employed in the control of permanent magnet synchronous motors (PMSMs) driven by a two-level voltage source inverter (2L-VSI). This technique offers low complexity and reduced torque ripples in the low-speed region by minimizing the duty-cycle of the applied voltage vector (VV) compared to the complete utilization of the DC-link voltage. However, it has its limitations, including slow torque dynamics, restricted modulation index (MI), and an inability to select zero VV, which would be useful for minimizing ripples in multilevel VSI drives. Additionally, it can lead to an unbalanced DC link due to the restricted VV selection, especially at low MI. To address these limitations, a modified PTC based on space vector pulse-width modulation approach is proposed for three-level neutral-point-clamped (3L-NPC) VSI-fed PMSM. The proposed 3L-PTC method can reduce torque and flux ripples at low MI, improve dynamic response, and maintain a balanced DC link regardless of operating conditions. Intensive numerical and experimental evaluations are carried out to validate the effectiveness of the proposed 3L-PTC.
Keywords: Dc-link; DC-link balancing; Modulation indexes; Permanent Magnet Synchronous Motor; Permanent-magnet synchronous motor drives; Predictive torque controls; Space vector PWM; Three level NPC inverter; Torque ripples; Voltage vectors; DC-link balancing; Permanent magnet synchronous motor; Predictive torque control; Space vector PWM; Three-level NPC inverter